2018
DOI: 10.1017/s0007123418000194
|View full text |Cite
|
Sign up to set email alerts
|

Launching Revolution: Social Media and the Egyptian Uprising’s First Movers

Abstract: Drawing on evidence from the 2011 Egyptian uprising, this article demonstrates how the use of two social media platforms – Facebook and Twitter – contributed to a discrete mobilizational outcome: the staging of a successful first protest in a revolutionary cascade, referred to here as ‘first-mover mobilization’. Specifically, it argues that these two platforms facilitated the staging of a large, nationwide and seemingly leaderless protest on 25 January 2011, which signaled to hesitant but sympathetic Egyptians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 48 publications
0
29
0
1
Order By: Relevance
“…Despite the fact that online activism is often condemned for its ineffectiveness (Barney, 2010;Gladwell, 2010;Morozov, 2011), a number of studies showed that social media can be an effective tool in mobilizing society into offline political actions, such as protests and even revolutions (Clarke & Kocak, 2020;Eaton, 2013;González-Bailón, Borge-Holthoefer, Rivero & Moreno, 2011;H. H.-s. Kim & Lim, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that online activism is often condemned for its ineffectiveness (Barney, 2010;Gladwell, 2010;Morozov, 2011), a number of studies showed that social media can be an effective tool in mobilizing society into offline political actions, such as protests and even revolutions (Clarke & Kocak, 2020;Eaton, 2013;González-Bailón, Borge-Holthoefer, Rivero & Moreno, 2011;H. H.-s. Kim & Lim, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Since clustering and influence in a network are determined by a tunable control parameter, we control for it. Finally, the initial size of protests is a reliable determinant of their final size [30,43] and is partially a lagged dependent variable, so we include it as well.…”
Section: Plos Onementioning
confidence: 99%
“…Recent datasets that specifically code protest episodes and states’ behaviors across dozens of countries also recreate the repression-dissent puzzle, as Figs 1 and 2 show. Fig 1 uses the Mass Mobilization (MM) dataset, which codes 13,060 protests with at least 50 attendees from 162 countries from 1990 through 2014 [ 43 ]. From that dataset, we model the size of protest as a function of protester violence and whether the state responds with accommodation, killing, arresting, shooting, or beating protesters; the model includes country and year fixed effects.…”
Section: The Persistence Of the Repression-dissent Puzzlementioning
confidence: 99%
See 1 more Smart Citation
“…39 Clarke and Kocak similarly indicate the role of social media in the mobilization of first movers during the Egyptian protests. 40 While I discuss the findings of these studies under grievances and opportunities for the purposes of providing links, their direct focus is not necessarily these factors. These studies benefit from the main tenets of the literature discussed above; however, some of them do not directly test for both grievances and opportunities while others test them only in single case settings.…”
Section: Explaining the Uprisings Through Grievances And Opportunitiesmentioning
confidence: 99%